Analysis Of Patient Satisfaction At Baki Health Center - Puji Hastuti; Sudarwati; Istiatin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to determine the significant influence between the competence of medical personnel, health facilities, patient waiting time and image on patient satisfaction. Apart from that, it is also to find out the significant simultaneous influence and which variables are the most dominant in influencing patient satisfaction at the Baki Health Center. The method used is a quantitative descriptive method. The population in this study was 100 patients and the entire population was sampled in this study, where the sampling technique used census sampling. The data used are primary data and secondary data with data collection techniques: observation, documentation, questionnaires and literature study. The data analysis technique in this research uses multiple linear tests. The research results show that the competency of medical personnel, health facilities, patient waiting time and image partially and significantly influence patient satisfaction. The advice from this research is that medical officers continue to improve the competency of medical personnel, health facilities, patient waiting times and image, so that patient satisfaction can continue to increase.